An overview of treatment strategies for class II and class III malocclusions - Almoabady, Ebraheem H.; Alzahrani, Sultan S.; Algrny, Ahmad J.; Aldhaban, Omar A.; Alshammari, Maha N.; Aldaghriry, Waad K.; Bagabir, Rgad A.; Alolaiqi, Fatimah F.; Alghamdi, Ali A.; Almaghlouth, Aisha; Altaf, Rehab W.; Alshehri, Riyadh M.; et al. (International Journal Of Community Medicine And Public Health, 2024)
Class II and class III malocclusions represent common yet complex dental conditions that affect both aesthetics and function. Managing these malocclusions requires an approach tailored to the patient's growth stage, with early interventions focusing on growth modification and adult cases often necessitating surgical solutions. In class II malocclusions, growth modification with functional appliances such as the Twin Block and Herbst appliance promotes mandibular advancement and improves facial harmony in younger patients. For older individuals or those with more severe malocclusions, orthodontic camouflage or mandibular advancement surgery, including bilateral sagittal split osteotomy, is recommended to achieve a balanced occlusal relationship and improve facial proportions. Class III malocclusions, often involving a prognathic mandible or maxillary deficiency, are particularly challenging. For young patients, facemask therapy and rapid maxillary expansion can encourage maxillary growth, while chin cup therapy can control mandibular projection, aiming to improve skeletal balance. In severe adult cases, combined orthodontic-surgical treatments, such as maxillary advancement through Le Fort I osteotomy or mandibular setback procedures, provide durable, functionally stable outcomes. Surgical-orthodontic approaches, including bimaxillary surgery, are particularly advantageous for severe class III cases by effectively addressing the underlying skeletal imbalances and enhancing facial aesthetics. Growth modification techniques emphasize the importance of early diagnosis and intervention, aiming to harness natural growth potential and reduce the need for more invasive treatments later in life. For adult patients, surgical interventions present a definitive solution, delivering substantial improvements in function and appearance. Ongoing advances in both orthodontic and surgical techniques are refining the precision and stability of treatment outcomes, underscoring the need for individualized, age-appropriate strategies in managing class II and class III malocclusions.